PENGUJIAN TOKSISITAS LIMBAH PELUMAS TERHADAP IKAN MAS (Cyprinus carpio) - Joni Hermana (Purifikasi, 2006)
The toxicity level of oil waste has not been identified as compared to the toxicity of lubricant oil. Therefore, the toxicity of oil waste was determined by using Gold fish (Cyprinus carpio) in a lab-scale ecotoxicity. The acute toxicity test was used as a method during the experiment which proceeded by the range finding tests to determine LC50 for 96 hours exposure. The concentration of 52,5 – 62,5% was applied for acute toxicity of oil waste and 61,0-68,5% was for lubricant oil. The result of experiment showed that LC50 for oil waste was (55,92 ± 1,04) mg/l and for lubricant oil was (64,80 ± 1,03) mg/l, hence it could be concluded that oil waste was more toxic than lubricant oil. Further, histopathology test showed that both samples, oil waste and lubricant oil, caused structural damage to the fish, which was shown by histopathological change of fish gills in the form of hyperplasia lamella.